Urgensi Keterangan Ahli dalam Memperkuat Kebenaran Bukti Digital: (Analisis Putusan Nomor 439 B/Pdt.Sus-Arbt/2016) - Angel Violita; Amelia Ruthmaya Tampubolon; Keisha Islami Pasha; Sri Handayani (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the urgency of digital expert testimony in strengthening the validity of electronic evidence in civil procedure law amid rapid technological transformation. The increasing use of digital communications, electronic transactions, and online documentation has given rise to new evidence in civil disputes, while its intangible and easily manipulated nature raises doubts about its authenticity and reliability. This study will focus on Decision Number 439 B/Pdt.Sus-Arbt/2016. The study relies on primary legal sources, legislation, court decisions, and secondary legal literature analyzed qualitatively. The findings show that electronic evidence is legally admissible when it meets the requirements of accessibility, integrity, authenticity, and accountability, but its probative value is highly dependent on technical validation. In the case analyzed, the petitioner's challenge to print the chat evidence was rejected because the allegations of manipulation were unsubstantiated and no expert testimony was presented to support the claim. This shows that expert testimony plays a decisive role in explaining technical aspects beyond the knowledge of the court and in strengthening the court's conviction. This study concludes that digital experts serve as a bridge between technological complexity and legal assessment, ensuring that digital evidence is evaluated objectively. The implication for courts and related parties is must prioritize the involvement of experts to promote legal certainty, factual truth, and fair dispute resolution.